Identification of the severe sepsis patient at triage: a prospective analysis of the Australasian Triage Scale. Issue 9 (11th December 2014) - Chamberlain, Diane J; Willis, Eileen; Clark, Robyn; Brideson, Genevieve
Abstract : Objective: This study aims to investigate the accuracy and validity of the Australasian Triage Scale (ATS) as a tool to identify and manage in a timely manner the deteriorating patient with severe sepsis. Methods: This was a prospective observational study conducted in five sites of adult patients. Keywords and physiological vital signs data from triage documentation were analysed for the 'identified' status compared with confirmed diagnosis of severe sepsis after admission to the intensive care unit. The primary outcome is the accuracy and validity of the ATS Triage scale categories to identify a prespecified severe sepsis population at triage. Secondary outcome measures included time compliance, antimicrobial administration and mortality prediction. Statistical analysis included parameters of diagnostic performance. Adjusted multivariate logistic regression analysis was applied to mortality prediction. Results: Of 1022 patients meeting the criteria for severe sepsis, 995 were triaged through the emergency department, 164 with shock. Only 53% (n=534) were identified at triage. The overall sensitivity of the ATS to identify severe sepsis was 71%. ATS 3 was the most accurate (likelihood ratio positive, 2.45, positive predictive value 0.73) and ATS 2 the most valid (area under the curve 0.567) category. Identified cases were more likely to survive (OR 0.81, 95% CI 0.697 to 0.94, p<0.007). The strongest bias-adjusted predictors of mortality were circulatory compromise variable (1.78, 95% CI 1.34 to 1.41, p<0.001), lactate >4 (OR 1.63, 95% CI 1.10 to 2.89, p<0.001) and ATS 1 category (OR 1.55, 95% CI 1.09 to 2.35, p<0.005). Conclusions: The ATS and its categories is a sensitive and moderately accurate and valid tool for identifying severe sepsis in a predetermined group, but lacks clinical efficacy and safety without further education or quality improvement strategies targeted to the identification of severe sepsis.